Legal Structure of Time Sharing System and Registration on Land Registry - F. Feza YILMAM Mendeş; Murat Mendeş; Yeşim Aliefendioğlu (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2017)
In this study, timesharing system is investigated in Turkey for obtaining holiday necessity which has optimal price and also some recommendations for registration of timesharing on land registry In this age people need resting because of hard ındustrial working conditions but also resting time is very short and resting cost is high .In that situation, the best model is time sharing system. It can supply what people need for vacation .This study tries to show benefits of the system also it includes some suggestions for developing constructive suggestions for registrating time sharing system on land registry and also how to be taken added tax.